2020
DOI: 10.2174/1574884714666190121154813
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Peripheral Neuropathy: A Narrative Review

Abstract: Background: Peripheral neuropathy is a painful condition deriving from many and varied etiologies. Certain medications have been implicated in the iatrogenic development of Drug Induced Peripheral Neuropathy (DIPN) and include chemotherapeutic agents, antimicrobials, cardiovascular drugs, psychotropic, anticonvulsants, among others. This review synthesizes current clinical concepts regarding the mechanism, common inciting medications, and treatment options for drug-induced peripheral neuropathy. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
80

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(132 citation statements)
references
References 64 publications
0
52
0
80
Order By: Relevance
“…Peripheral neuropathy is a painful condition deriving from many and varied etiologies (38, 39). Certain medications have been implicated in the iatrogenic development of drug induced peripheral neuropathy (DIPN) and include chemotherapeutic agents, antimicrobials, cardiovascular drugs, psychotropic, anticonvulsants, among others (39).…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral neuropathy is a painful condition deriving from many and varied etiologies (38, 39). Certain medications have been implicated in the iatrogenic development of drug induced peripheral neuropathy (DIPN) and include chemotherapeutic agents, antimicrobials, cardiovascular drugs, psychotropic, anticonvulsants, among others (39).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, neuropathy is one of the most frequent chemotherapy-related complications [17]. Chemotherapy-induced neuropathic pain is highly refractory to drugs such as opioids, tricyclic antidepressants, and anticonvulsants, as is diabetic neuropathic pain [18].…”
Section: Kampo For Treatment Of Neuropathic Painmentioning
confidence: 99%
“…Among cardiovascular drugs, the cholesterol‐lowering statins (simvastatin, pravastatin and fluvastatin) seem to have significant risk factors for the development of primary sensory neuropathy (Jones et al, 2019). However, only a few clinical trials or meta‐analysis studies have identified statin‐related peripheral neuropathy, which was predominantly of the sensory type (summarized in the review of Jones et al, 2019), and the mechanism is also largely unknown. It is supposed to be associated with energy depletion of neurons due to decreased ubiquinone synthesis.…”
Section: Co‐morbidities Simultaneously Affecting the Sensory Nerves Amentioning
confidence: 99%
“…However, their well‐known cardioprotective and anti‐atherosclerotic effects are far outweigh the sporadic appearance of statin‐derived sensory neuropathy. Also, the anti‐arrhythmic drug, amiodarone, in high dose and over a long duration has a risk of causing sensory and motor deficits in patients (Jones et al, 2019).…”
Section: Co‐morbidities Simultaneously Affecting the Sensory Nerves Amentioning
confidence: 99%